Analisis Resiko Dan Laporan Keuangan Serta Penanganannya Pada UMKM Tapis Kilu Andan Di Desa Baturaja Kecamatan Way Lima - Lilyana, Besti; Anwar, Mashuril; Noviyanti, Dewi (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
MSMEs have a strategic role in supporting local economic growth, but still face various challenges, especially in terms of risk management and financial records. This community service activity aims to help MSME Tapis Kilu Andan in Baturaja Village, Way Lima District, in identifying business risks, preparing simple financial reports, and designing strategies for handling them. The implementation method includes field observation, interviews, training, and direct assistance to business actors. The results of the activity show that MSMEs face several major risks, such as dependence on raw materials, limited market access, and the absence of adequate financial records. Through training and assistance, MSME actors began to understand the importance of financial management and were able to prepare basic financial reports such as cash flow and profit and loss. In addition, a risk mitigation strategy was also designed based on participatory discussions. This activity has a positive impact on increasing awareness, knowledge, and capacity of MSME actors in managing their businesses more systematically and sustainably.